2017
DOI: 10.1039/c7cc07990g
|View full text |Cite
|
Sign up to set email alerts
|

The role of symmetry breaking in the structural trapping of light-induced excited spin states

Abstract: Light-Induced Excited Spin State Trapping (LIESST) data are reported for seven isostructural solvate salts from the iron(ii)/2,6-di(pyrazol-1-yl)pyridine family. A complicated relationship between their spin-crossover T and T(LIESST) values may reflect low-temperature thermal and light-induced symmetry breaking, which is shown by one of the compounds but not by two others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 27 publications
2
70
0
Order By: Relevance
“…The latter is the only structure:function relationship we have identified which accounts for all the outlier compounds in group 3. We therefore suggest the Fe N bond lengths in the high-spin state are the biggest contributor to 39 That gives a predicted T(latt) = 147 K, or T½(solid) = 68 K, from the correlation in Figure 4. SCO in [Fe(1-bpp)2] 2+ and [Fe(3-bpp)2] 2+ derivatives rarely extends below 100 K, [39][40][41] where they become kinetically trapped in their high spin states.…”
Section: T½(solid)mentioning
confidence: 79%
“…The latter is the only structure:function relationship we have identified which accounts for all the outlier compounds in group 3. We therefore suggest the Fe N bond lengths in the high-spin state are the biggest contributor to 39 That gives a predicted T(latt) = 147 K, or T½(solid) = 68 K, from the correlation in Figure 4. SCO in [Fe(1-bpp)2] 2+ and [Fe(3-bpp)2] 2+ derivatives rarely extends below 100 K, [39][40][41] where they become kinetically trapped in their high spin states.…”
Section: T½(solid)mentioning
confidence: 79%
“…Deviations from the "family line" can also find their origin not at the coordination sphere scale but at the crystal packing scale. For example, recently, compounds from the bpp family [Fe(L 1 ) 2 ](BF 4 ) 2 ·S were shown to deviate from the T 0 = 150 K line due to a photo-induced crystallographic phase transition [41]. Various solvates of the [Fe(…”
Section: Iii2-further Predictive Abilitiesmentioning
confidence: 99%
“…However, such deviation can also come from crystal packing effects. We mentioned the occurrence of a structural transition upon irradiation [41] and also the effect of internal pressure due to metal dilution [29]. Depending on the size of the host ion [57], the internal pressure can be tuned and the effect on the T(LIESST) recorded.…”
Section: Iv2-t(liesst) Is Not a Critical Temperature!mentioning
confidence: 99%
“…Previous studies have demonstrated an empirical relation between T 1/2 and T (LIESST): T (LIESST)= T 0 −0.3× T 1/2 , with T 0 =150 K for tridentate ligands such as the bpp ligand ,,,. Taking for T 1/2 the mean value of T 1/2↓ and T 1/2↑ , T 1/2 can be evaluated at 392 and 425 K respectively for the two hysteresis cycles.…”
Section: Resultsmentioning
confidence: 99%